Drinkers, non-drinkers and deferrers: Reconsidering the beer/footy couplet amongst Australian Rules football fans - Thompson, Kirrilly (The Australian journal of anthropology, 2011)
There is a common perception that football and alcohol go hand in hand and that players and fans routinely engage in excessive and irresponsible drinking. In Australia, this is manifest in the stereotypical ‘Pissed Aussie Rules fan’. Following research with Australian Rules football fans in South Australia, we identified three categories of fans according to their (non)engagement with alcohol: Drinkers, Non-Drinkers and Deferrers. Deferrers were self-identified drinkers who separated alcohol consumption from spectating, for fear of ‘contamination’. Our identification of counter-stereotypic ways in which fans engage with alcohol (or not) challenges the assumptive worlds in which popular commentary on football and drinking operates. This was, to our knowledge, the first ethnography of drinking behaviour amongst Australian Rules football fans. It demonstrates the advantage of using ethnographic research techniques to understand the relationship between identity and consumption.